The Occupational Selection of Emigrants - Alexander Patt; Miguel Flores; Jens Ruhose; Simon Wiederhold (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
The current literature that investigates the selection of Mexican migrants to the United States focuses on selectivity in educational attainment and earnings. Notably absent from the literature is evidence on occupational selection, because it is unclear how to measure the skill content of Mexican occupations. However, any such research would yield important insights regarding the selection on labor-market skills that Mexicans carry with them to the United States. We use data from a representative Mexican worker survey—equivalent to the U.S. O*NET—to develop novel measures of cognitive and manual skills for migrants based on their pre-migration occupational history, and compare them to the skills of Mexicans who do not migrate. Using detailed longitudinal micro-level data from two Mexican labor surveys, the Mexican Migration Project, and the Mexican Family Life Survey, our analysis consistently shows that migrants have lower cognitive and higher manual skills than non-migrants. This finding is robust to controlling for age, gender, and educational attainment and also holds within broader occupational groups. Despite substantial changes in emigration rates over time, we also document that occupational selection is highly persistent.
Keywords: F22; O15; J61; 330